2015
DOI: 10.1111/jch.12492
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pulse Wave Velocity and a Marker of Renal Tubular Damage (N‐Acetyl‐β‐D‐Glucosaminidase) in Patients Without Diabetes

Abstract: The authors assessed the association between the ratio of urinary activity of N-acetyl-b-D-glucosaminidase (NAG) to creatinine and the brachial-ankle pulse wave velocity (baPWV) in patients without overt diabetes mellitus (DM). This was a cross-sectional study of 233 patients who had an estimated glomerular filtration rate (eGFR) ≥30 mL/min/ 1.73 m 2 and no history of kidney disease. Patients were divided into two groups: high NAG group (>5.8 U/g creatinine) and low NAG group (≤5.8 U/g creatinine). Mean baPWVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Even before the development of albuminuria, uNAG excretion was found to be positively correlated with hyperglycemia and diabetes duration 5 . Among our T1D subjects, the median uNAG level (5.6 U/g creatinine) fell within the reported range of values in various populations with diabetes (2.0–10.1 U/g creatinine), which was close to the range reported in a study of T1D subjects of similar age 18 , 23 25 . In accordance with previous findings, age was the most important determinant of uNAG level with significant linear correlation in this study, followed by poor glycemic control (A1c or GA level) and degree of albuminuria (ACR) in the submicroalbuminuric range.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Even before the development of albuminuria, uNAG excretion was found to be positively correlated with hyperglycemia and diabetes duration 5 . Among our T1D subjects, the median uNAG level (5.6 U/g creatinine) fell within the reported range of values in various populations with diabetes (2.0–10.1 U/g creatinine), which was close to the range reported in a study of T1D subjects of similar age 18 , 23 25 . In accordance with previous findings, age was the most important determinant of uNAG level with significant linear correlation in this study, followed by poor glycemic control (A1c or GA level) and degree of albuminuria (ACR) in the submicroalbuminuric range.…”
Section: Discussionsupporting
confidence: 89%
“…uNAG was measured by an enzymatic method (Nittobo Medical, Fukushima, Japan) using a JCA-BM 6010/c automated chemistry analyzer (JEOL Ltd, Tokyo, Japan). A high uNAG level was defined using 5.8 U/g creatinine as a dichotomized cutoff, based on the upper normal value in a study of the Japanese population (normal range: 1.6 U/g to 5.8 U/g creatinine) 18 .…”
Section: Methodsmentioning
confidence: 99%
“…That study investigated patients with T2D during a median follow-up of 7 years and showed that urinary NAG is comparable to albuminuria as an indicator of the preexistence and development of severe macrovascular disease, including myocardial infarction and peripheral vascular disease. Regarding subjects without diabetes, Ouchi et al [ 23 ] reported that elevated urinary NAG is related to elevated arterial stiffness assessed by brachial-ankle PWV. In a study including a low-risk general population, urinary NAG and ACR were independently associated with first-ever myocardial infarction, first-ever ischemic stroke, and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased urinary NAG is a sensitive marker of tubular injury related to inflammation and oxidative stress [ 24 ]. Therefore, the elevation of urinary NAG, a renal interstitial marker, might reflect the severity of interstitial changes that result from atherosclerosis and subsequent ischemic injury [ 23 ]. In addition, the association between urinary NAG and carotid IMT might be mediated by several common risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary NAG, albumin, and glucose levels were expressed as uNAG-to-creatinine ratio and ACR to minimize the influence of variance in kidney function. Urinary NAG activity was considered abnormal when >5.8 U/g creatinine [ 10 ]. Urinary NAG was measured using a reagent from Nittobo Medial Co. Ltd. (Tokyo, Japan) and a JCA-BM 6010/c automated chemistry analyzer (JEOL Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%